Primacy within the Church. Ecclesiological Presumptions and Church Practice in the First Millennium (Orthodox Aspect) - Мидић, Игнатије (Sabornost - The Theological Year-book, 2016)
For the right understanding of primacy within the Church and of Church practice in relation to primacy before the Great Schism of 1054, it is necessary, to consider two problems: perception of the Church, and perception of Apostolic Succession‑Tradition in Church history of the first millennium. The Synod deals with matters which insure Eucharistic unity in the form of Apostolic Tradition. However, Apostolic Tradition in all its aspects: in consecration of bishops, in teaching, and in its missionary activity, is always connected with the Eucharist with which it is being identified.